Modernization of the plant - control of the compressor motor speed - Pašić, Muhamed H.; Ružić, Dragana R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper describes the modernization by installing frequency converters, their  features and benefits as well as the disadvantages of the existing solutions and the advantages of the upgraded status. The existing state was such that the motors were switched on through the contactor and were always working at full capacity. In the new solution, one motor will be switched on through frequency converters, thus working with a particular intensity, depending on the need. This will bring savings in power consumption as well as in the maintenance. Introduction Modernization of the equipment using frequency converters will bi discussed on the electric motor drive (EMP) for the air production for professional use in the industry. Description of the existing systems and the procedures provided for modernization The air production system consists of two three-phase asynchronous motors of 7.5 kW driving the air production turbine. Given the fact that the motors are driven directly (one contactor), this represents the involvement of either only 50% or 100% of the air production capacity. For a finer air control, relief valves are used. Installing a frequency converter could result in regulating the amount of air produced and there would be no loss to the relief valve. Under the proposed solution for controlling compressor motors, one motor would remain attached to the direct start while the other would be controlled via the frequency converter. Characteristics of frequency converters To change the speed of asynchronous motors, we use the special electronic power devices, so-called frequency regulators that are connected between the electric motor and the electric grid. Frequency regulators convert voltage of constant amount and frequency of the electric grid into a variable amount of voltage and frequency. They change the rotational speed of asynchronous motors depending on a required technological process. Frequency controllers for harmonizing the rotary speed induction motors simultaneously changing the frequency and voltage can be: a) direct converters b) indirect converters Indirect frequency converters consist of the following components: • rectifiers,• direct current links,• inverters,• steering wheels. Method of setting the speed of frequency converters An instant connection and a preferred (required) value can be defined in several ways: • the control panel start, start and stop button; the frequency (speed) using the default• via: the control terminals (lattices with programmable inputs / outputs), start and stop are defined by closing the contact connected to the correct terminals; frequency (speed) of the default analog signal; potentiometer or an analog signal from the process, PLC or the direct gauge of the analog value • via the communication interface. Selecting and programming frequency converters Frequency converters for air production for electric plants are selected on the basis of the asynchronous motor nameplate, so we chose Danfoss frequency converter manufacturers, trademark VLT 2875 ST. When programming the frequency converter, we used digital inputs 18 and 27 and the digital outputs are used to display the alarm in case of failure of this drive. Benefits of plant control via frequency converters Monitoring Frequency converters can monitor and manage the process that can intervene in case of disturbances. Monitoring can be divided into three categories: • supervision of Electric Drives • motor monitoring • supervision of the frequency converter Improvements Frequency regulators save electric power so that at all times the speed of motor rotation conforms to the electrical drive. Frequency converters help producing exactly as much air in the system as required for a normal operation depending on a number of consumers connected to the system. Conclusion By examining the operation of the EMP which seemingly worked correctly, it was found that it was using about 50% more electricity than needed. It has been established that the installation of frequency controllers reduce losses, extend the service life with minimal investment and the return on investment is short.
Keywords: plants; modernization; frequency converter; Converters; Compressors